Mentoring Digital Content Creation in High School Entrepreneurship Lessons in Indonesia - Mamuaya, Nova Ch.; Susanto, Sherly Ernawati; Siregar, Barham; Zsazsa, Cut Sah Kha Mei; Widodo, Hadi (Journal Of Human And Education (JAHE), 2025)
Abstract The author's idea to conduct monitoring with the theme of becoming a digital content creator is included in every entrepreneurship subject in high schools in especially at SMA 1 Manado & SMK 1 Medan Indonesia. The result in this study show the author has a special scheme in mentoring students with the eight materials presented above. The eight materials are delivered within a period of two weeks with the provision that one theme is delivered full one day alternately. The author believes that the seven themes can be a stimulus for high school students throughout Indonesia to become digital content creators. Keyword : Mentoring, Digital, Content Creation